2022
DOI: 10.3389/fsufs.2022.974215
|View full text |Cite
|
Sign up to set email alerts
|

Landscape or local? Distinct responses of flower visitor diversity and interaction networks to different land use scales in agricultural tropical highlands

Abstract: Land use change has been identified as a cause for biodiversity loss and has significant effects on pollinators and their interactions with plants. Interaction network analyses complement diversity estimators by providing information on the stability and functionality of the plant-pollinator community in an ecosystem. However, how land use changes affect insect diversity, and the structure of their plant-insect interaction networks, could depend on the intensity of the disturbance but also may be a matter of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 104 publications
1
4
0
Order By: Relevance
“…Several studies on coffee have already observed the positive effect of the proximity of natural areas on the diversity of floral visitors (Bravo‐Monroy et al 2015; Ricketts 2004; Ricketts et al 2008). Other studies in coffee plantations have also shown that wild bees, especially the social ones as stingless bees, were enhanced in the presence of high shade coffee and tree diversity, as in our agroecological sites (González‐Chaves et al 2020; Jha & Dick 2010; Jha & Vandermeer 2009, 2010; Munyuli 2011) and floral resource availability (Escobedo‐Kenefic et al 2020, 2022; Landaverde‐González et al 2017). This proximity and higher proportion of natural areas in our study sites could have contributed to favoured pollination by wild bees.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Several studies on coffee have already observed the positive effect of the proximity of natural areas on the diversity of floral visitors (Bravo‐Monroy et al 2015; Ricketts 2004; Ricketts et al 2008). Other studies in coffee plantations have also shown that wild bees, especially the social ones as stingless bees, were enhanced in the presence of high shade coffee and tree diversity, as in our agroecological sites (González‐Chaves et al 2020; Jha & Dick 2010; Jha & Vandermeer 2009, 2010; Munyuli 2011) and floral resource availability (Escobedo‐Kenefic et al 2020, 2022; Landaverde‐González et al 2017). This proximity and higher proportion of natural areas in our study sites could have contributed to favoured pollination by wild bees.…”
Section: Discussionsupporting
confidence: 77%
“…At the same time, the presence of other floral heterogeneous resources such as co‐flowering crops can cause competition and stress within coffee crops, more strongly affecting the availability in coffee of social bees such as honeybees and stingless bees (Bänsch et al 2021; Geeraert et al 2019; Ludewig, Götz, et al 2023; Peters et al 2013; Ricketts 2004; Veddeler et al 2006). However, these are hypotheses that are out of the scope of this study and future studies that consider the effect of floral heterogeneity at landscape and local scales (Escobedo‐Kenefic et al 2022) and competition between species in cash crops should be assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the long term, an even more intense reduction in diversity can be observed, also impacting generalist species ( Burkle & Knight, 2012 ). Furthermore, the increase and lack of effect on nestedness in the 11 presented studies could be linked to the concentration of interactions by generalist species, both in plants and pollinators ( Jauker et al, 2019 ; Díaz Infante, Lara & Arizmendi, 2020 ; Morrison & Dirzo, 2020 ; Motivans Švara et al, 2021 ; Escobedo-Kenefic et al, 2022 ).…”
Section: Discussionmentioning
confidence: 87%
“…Regarding the effects of anthropization on the structural patterns of interaction networks, previous research supports our results, concluding that the metrics used are particularly sensitive to environmental changes ( Aguilar et al, 2009 ; Ferreira, Boscolo & Viana, 2013 ; Soares, Ferreira & Lopes, 2017 ). However, contrary to our findings, other studies have indicated that empirical data available suggest that nestedness is not affected by habitat disturbance ( e.g ., Hagen & Kraemer, 2010 ; Jauker et al, 2019 ; Morrison & Dirzo, 2020 ; Escobedo-Kenefic et al, 2022 ). Instead, H 2 ’ metrics show responses similar to those obtained in this study.…”
Section: Discussionmentioning
confidence: 99%